2022
DOI: 10.2166/h2oj.2022.037
|View full text |Cite
|
Sign up to set email alerts
|

Container-based sanitation in urban Haiti: how can it improve human rights as a component of citywide inclusive sanitation?

Abstract: Health, sanitation, and livelihoods are interrelated human rights and essential components of community wellbeing. Despite the United Nations recognizing the human right to sanitation, one-third of the world's population lack access to improved sanitation. Furthermore, in many low- and middle-income countries, urban latrines are excavated manually without physical or regulatory protections. Container-based sanitation (CBS) has promise as a component of Citywide Inclusive Sanitation (CWIS) in densely populated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Further, dissatisfaction was not identified as a meaningful driver of attrition from CBS services which aligns with other studies that have found low dissatisfaction with CBS in serviced areas (World Bank, 2019;Tidwell et al, 2022). This low dissatisfaction may be due to CBS organizations' practice of collaboratively designing their sanitation systems based on feedback from their customers (e.g., Mijthab et al, 2021;VanRiper, 2021). Indeed, previous literature suggests that CBS services can satisfy subscriber's wants and needs for sanitation (Russel et al, 2019).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Further, dissatisfaction was not identified as a meaningful driver of attrition from CBS services which aligns with other studies that have found low dissatisfaction with CBS in serviced areas (World Bank, 2019;Tidwell et al, 2022). This low dissatisfaction may be due to CBS organizations' practice of collaboratively designing their sanitation systems based on feedback from their customers (e.g., Mijthab et al, 2021;VanRiper, 2021). Indeed, previous literature suggests that CBS services can satisfy subscriber's wants and needs for sanitation (Russel et al, 2019).…”
Section: Introductionsupporting
confidence: 68%
“…Whereas, SEs generate enough revenue to sustain their operations independently through their business model or through a mix of revenue generating activities and grants (Luke and Chu, 2013;Doherty et al, 2014). CBS organizations often provide sanitation services in locations where a government utility currently does not provide services (Mijthab et al, 2021;VanRiper et al, 2022c) and where individual sanitation users may struggle to afford subsidized costs of safely managed sanitation services (VanRiper et al, 2022a). Therefore, gathering reliable income solely from external sources (e.g., government funds or grants) or full funding from internal subscribers is difficult (World Bank, 2019).…”
Section: Cbs Providers As Non-profit Organizations and Social Enterpr...mentioning
confidence: 99%
See 2 more Smart Citations